2012
DOI: 10.1111/j.1365-4632.2011.05229.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous sporotrichosis: a six‐year review of 19 cases in a tertiary referral center in Malaysia

Abstract: Lymphocutaneous sporotrichosis was the most common subtype of cutaneous sporotrichosis in our series, with cat scratches or bites being the most common preceding trauma. Oral itraconazole was highly effective for the localized subtypes, whereas intravenous amphotericin B was required in disseminated cutaneous sporotrichosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 31 publications
1
50
2
3
Order By: Relevance
“…In this study, 8/44 isolated strains exhibited the ability to grow at 37℃(thermotolerant) , which suggests that upon establishment of the infection in the human host, about one-fifth of the patients would contract the lymphocutaneous form instead of the fixed cutaneous disease. This is in contrast to another retrospective study that reported that all human cases of sporotrichosis in Malaysia attributable to cat bites or scratches were presented with the lymphocutaneous form 13) .…”
Section: Thermo-tolerance Of Clinical Isolates From Malaysiacontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, 8/44 isolated strains exhibited the ability to grow at 37℃(thermotolerant) , which suggests that upon establishment of the infection in the human host, about one-fifth of the patients would contract the lymphocutaneous form instead of the fixed cutaneous disease. This is in contrast to another retrospective study that reported that all human cases of sporotrichosis in Malaysia attributable to cat bites or scratches were presented with the lymphocutaneous form 13) .…”
Section: Thermo-tolerance Of Clinical Isolates From Malaysiacontrasting
confidence: 99%
“…Since then, multiple reports of sporotrichosis in human patients have been published in Malaysia. Among these, a retrospective study reported 13/19 cases that were associated with preceding trauma, half of which were directly attributable to cat scratches or bites 13) . This highlights the role of cats not only as propagators but also as a significant risk factor for acquiring this disease in Malaysia, as similarly reported in other countries like Brazil and India 14−17) .…”
Section: Sporothrichosis In the Malaysian Veterinary Contextmentioning
confidence: 99%
“…Puede presentarse a cualquier edad, siendo más común en niños y adultos jóvenes, especialmente entre los 16 a 35 años (cuadro 1) (3,9,11). Sin embargo, hay una publicación del 2011 que reporta 15 casos de esporotricosis en niños menores de 10 meses de edad (12).…”
Section: Introductionunclassified
“…Sin embargo, hay una publicación del 2011 que reporta 15 casos de esporotricosis en niños menores de 10 meses de edad (12). Algunos estudios reportan una predominio en los hombres, lo cual podría corresponder a las actividades de campo que estos realizan; caso contrario se ha visto en la India y Japón, donde las mujeres son las más afectadas, probablemente por su participación activa en actividades al aire libre en estos países (3,9,11 La esporotricosis es la micosis subcutánea más frecuente, tiene una distribución mundial, siendo más común en áreas tropicales y subtropicales.…”
Section: Introductionunclassified
“…34 The unexpected histopathological findings in Case 1 were reviewed and corrected to conclude that SCC was not present.…”
Section: -28mentioning
confidence: 99%